Uqud al-Khidmah and the Protection of Domestic Workers: A Comparative Study between Fiqh and Indonesian Positive Law - Eva Fadhilah; Pitrotussaadah Pitrotussaadah (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
The issue of legal protection for domestic workers (PRT) in Indonesia remains a pressing concern, as this group has yet to receive comprehensive recognition in national legislation. This study aims to analyze the concept of uqud al-khidmah in Islamic jurisprudence (fiqh) and compare it with Indonesian positive law regarding the legal protection of domestic workers. A normative qualitative approach is employed, examining classical and contemporary Islamic legal sources alongside relevant Indonesian legal instruments, including Ministerial Regulation No. 2 of 2015 on the Protection of Domestic Workers. In Islamic law, ijarah or uqud al-khidmah contracts emphasize principles such as justice, mutual consent (an taradin), the avoidance of ambiguity (gharar), and respect for human dignity, all of which reflect a holistic framework for worker protection. In contrast, Indonesia’s positive law has yet to provide full protection, due to the absence of a specific law governing domestic work. The findings reveal that fiqh offers significant normative contributions to formulating just and humane regulations for domestic workers. Therefore, integrating Islamic legal values into national policymaking may serve as a constructive alternative to address the existing legal vacuum and enhance the protection of this vulnerable labor sector.